Uma análise sobre o acesso e uso de informações em saúde via internet pelas pessoas idosas - Orlandi, Brunela Della Maggiori (2014)
Scientific and technological advances bring individual and collective psychosocial implications. Thus, the inclusion of the elderly in the context of development of new technologies of information and communication is needed. The present study investigated whether participants do searches about health on the internet and how these searches influence the life quality of the elderly, relating the reported diseases, considering the CTS field perspective and the area of gerontology. In this sense, the aim of this study was to analyze the access and use of health information through a technological resource, by a group of elderly people from a program of digital inclusion, in this case the Programa de Inclusão Digital (PID) of the Fundação Educacional de São Carlos (FESC) which is a government entity created to develop and promote educational programs for all ages. The study was conducted in seven steps, been the data collection divided into three phases. In the first phase of data collection, after the approval of the Committee of research ethics, an invitation to participants was done, having attended 19 elderly people, 8 male and 11 female on which they answered a semistructured questionnaire. For the second stage 8 elderly people participated in a directed study, in which issues of access to health information through the internet were addressed. In the third phase the data collection was done through a focus group divided into 2 men and 4 women. The main results show that the average age of the elderly is 67 years old, with college degree and earning up to three minimum wages, from the participants only 1 doesn t have a computer with internet access at home and those who own do searches for information and news. The study also shows that the participants of the third stage believe that the search for health information on the internet is important and influences their life quality.